Hemophilia carrier’s awareness, diagnosis, and management in emerging countries: a cross-sectional study in Côte d’Ivoire (Ivory Coast) - Catherine Lambert; N’ Dogomo Meité; Ibrahima Sanogo; Sébastien Lobet; Eusèbe Adjambri; Stéphane Eeckhoudt; Cedric Hermans (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Little data is available on awareness of hemophilia carrier condition or associated bleeding risk and management in Sub-Saharan African countries. This study sought to identify hemophilia carriers in Côte d’Ivoire in order to collect data on demographics, bleeding phenotype, and laboratory results. Another purpose was to provide Ivorian hemophilia carriers with counseling on their risk of bleeding and of having children with hemophilia. A 12-month prospective study was conducted involving Ivorian hemophilia carriers recruited trough pedigree analysis pertaining to 81 hemophilia patients followed-up at the Yopougon Hemophilia Treatment Center in Abidjan. They were assessed using in-depth interviews, pedigree analysis, and laboratory testing. Results Sixty-one subjects comprising 27 obligate and 34 possible carriers were recruited. None had previously been assessed, with 64% unaware of their carrier status despite a familial history of hemophilia in 69%. The most frequently reported bleeding symptom was menorrhagia (31%). Prolonged bleeding was reported after vaginal delivery in 19.6%, post-surgery in 4.9%, and post-dental extraction in 4.9%. Only one carrier was treated with tranexamic acid, with no other hemostatic therapy recorded. The median (range) clotting FVIII was 0.85 IU/mL (0.24–1.90 IU/mL) and FIX 0.60 IU/mL (0.42–1.76 IU/mL) in hemophilia A and B carriers, respectively. HA carriers had a FVIII < 0.5 IU/mL in 12.5%. Conclusions This study highlights the need of implementing care for hemophilia carriers in developing countries, and the high value of pedigree analysis for carrier identification, along with the relevance of diagnosis, treatment, and education of carriers, families, and caregivers.